Globalization, productivity growth, and labor compensation - Christian Dreger; Marius Fourné; Oliver Holtemöller (Halle Institute for Economic Research (IWH), 2023)
We analyze how changes in international trade integration affect productivity and the functional income distribution. To account for endogeneity, we construct a leaveout measure for international trade integration for country-industry pairs using international input-output tables. Our findings corroborate on the country-industry level that international trade integration increases productivity. Moreover, we show that both trade in intermediate inputs and trade in value added is associated with lower labor shares in emerging markets. For advanced countries, we document a positive effect of trade in value added on the labor share of income. Further, we show that the effects on productivity and labor share are heterogeneous across different sectors. Finally, we discuss the implications of our results for a possible throwback in international trade integration due to experiences from recent crises.
Keywords: F4; F6; J3; 330; global value chains; globalization; income distribution; labor share; productivity